The role of leptospiral proteins in immune evasion and inflammatory response stimulation in HEK293T cell monolayers - Silva, Igor R. M.; Teixeira, Aline F.; Nascimento, Ana L. T. O. (Frontiers in Immunology, 2025)
Pathogenic Leptospira spp. are the causative agents of leptospirosis, a significant zoonotic disease that has emerged as a crucial public health concern. This study aims to evaluate the interactions of two L. interrogans proteins, LIC_10499 and LIC_12339, with host components as well as with endothelial and epithelial cells. The coding sequences (CDSs) for LIC_10499 and LIC_12339 were cloned, expressed in Escherichia coli, and successfully purified from inclusion bodies. Both recombinant proteins demonstrated interactions with fibronectin, fibrinogen, and plasminogen (PLG). Notably, these proteins were capable of sequestering PLG from normal human serum (NHS). In the presence of an activator, the bound PLG is converted to plasmin (PLA), a broad-spectrum protease involved in pathogen invasion and immune evasion. Additionally, LIC_10499 and LIC_12339 were found to bind to complement system regulators, including factor H and C4b-binding protein, as well as to components C7, C8, and C9. We observed that the formation of C9 complexes was inhibited in the presence of recombinant proteins, and a higher survival rate of E. coli was noted when the proteins were incubated with NHS. The protein rLIC_10499 was able to bind to both monolayer and suspension cells of HMEC, Ea.hy926, and HEK293T, whereas rLIC_12339 only bound to HEK293T suspension cells. A significant production of IFN-γ was detected after 24 h when HEK293T epithelial cells were incubated with rLIC_10499, while a modest production of IL-6 and IL-8 was observed. No cytokine production occurred when HEK293T cells were stimulated with rLIC_12339. Collectively, these findings suggest that these proteins play a role in leptospiral immune evasion and have the potential to induce an inflammatory response in host cell monolayers.